Relationship between preferred saddle height and pedalling kinematics in professional cyclists - Millour, G.; Duc, S.; Segui, D.; Theo, O.; Frederic, P.; William, B. (Journal of Science and Cycling, 2019)
Background: Proper saddle height in cycling can improve health, comfort, and performance (Millour et al. 2019). Methods based on knee angle (KA) for saddle height adjustment are frequently employed (Ferrer-Roca et al. 2011). They are considered accurate because they consider individual differences in thigh, shank, and foot length (Bini and Hume 2016). Ferrer-Roca et al. (2011) advocate KA between 30° and 40° during maximum knee extension while pedalling to prevent injuries. However, this method does not consider ankle angle (AA) which can vary considerably according to the individual pedalling technique (Peveler et al. 2012).